2019
DOI: 10.1101/694661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic resonance measurements of cellular and sub-cellular membrane structures in live and fixed neural tissue

Abstract: We develop magnetic resonance (MR) methods for measuring real-time changes of tissue microstructure and membrane permeability of live and fixed neural tissue. Diffusion and exchange MR measurements are performed using the large static gradient produced by a single-sided permanent magnet. Using tissue delipidation methods, we show that water diffusion is restricted solely by lipid membranes. Most of the diffusion signal can be assigned to water in tissue which is far from membranes. The remaining 25% can be ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 110 publications
2
16
0
Order By: Relevance
“…While exchange time τ ex > 1000 ms was in vivo measured in lenticular nucleus and thalamus using FEXI (Lampinen et al, 2017), and τ ex 115 ms was found between extra-neurite space and astrocytes in vitro (Yang et al, 2018), much shorter exchange time range τ ex 10-30 ms was recently found in human gray matter on a human Connectome scanner in the high-b regime, at b 25 ms/µm 2 (Veraart et al, 2018). Furthermore, exchange times of about 10 ms were found in live and fixed excised neonatal mouse spinal cord between membrane structures and free environments using DEXSY (Williamson et al, 2019). Therefore, we speculate that human gray matter may be in the crossover regime, where the exchange effects compete with those of the structural disorder (Node 2.2.2); in this picture, exchange is likely to affect the numerical coefficients, such as D ∞ , c D and c K , whereas the qualitative t −1/2 power-law scaling is determined by the structural disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While exchange time τ ex > 1000 ms was in vivo measured in lenticular nucleus and thalamus using FEXI (Lampinen et al, 2017), and τ ex 115 ms was found between extra-neurite space and astrocytes in vitro (Yang et al, 2018), much shorter exchange time range τ ex 10-30 ms was recently found in human gray matter on a human Connectome scanner in the high-b regime, at b 25 ms/µm 2 (Veraart et al, 2018). Furthermore, exchange times of about 10 ms were found in live and fixed excised neonatal mouse spinal cord between membrane structures and free environments using DEXSY (Williamson et al, 2019). Therefore, we speculate that human gray matter may be in the crossover regime, where the exchange effects compete with those of the structural disorder (Node 2.2.2); in this picture, exchange is likely to affect the numerical coefficients, such as D ∞ , c D and c K , whereas the qualitative t −1/2 power-law scaling is determined by the structural disorder.…”
Section: Discussionmentioning
confidence: 99%
“…For neurons and glial cells grown on polysterene beads, the exchange time was recently estimated to be τ ex ≈ 115 ms (Yang et al, 2018). In live and fixed excised neonatal mouse spinal cord, Williamson et al (2019) observed the water exchange rate ∼ 100 s −1 between membrane structures and free environments. Measurement for diffusion times of the order of or exceeding 100 ms may thereby be affected by the physics of exchange.…”
Section: Diffusion Model Selection Decision Treementioning
confidence: 99%
“…Furthermore, advanced MRI hardware, utilizing stronger diffusion gradients such as those available in the CONNECTOM scanner, 49 may allow the exploration of an additional dimension, the diffusion time, that may carry unique information about microstructural features such as membrane permeability, spatial disorder and more (see further the earlier Diffusion Time Section). Promising future applications may involve the multidimensional exploration of sub‐cellular membrane structures 168 or the combined diffusion‐relaxation of brain metabolites. 169 , 170 …”
Section: Applicationsmentioning
confidence: 99%
“…While many methods have been proposed to extract information on fiber crossing [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and density morphology of white matter, 27 methods for our concern are in the early stages of development. 28,29 It is straightforward to solve a direct problem, that is, to compute the dMRI signal for the molecules diffusing among a given 3-dimensional mesh of obstacles. One can expect that the linear size of these obstacles, R, contributes to the significant changes of the signal at a time scale Δ ∼ R 2 ∕D , where D is the self-diffusion coefficient in the fluid surrounding the obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The general approach is to acquire high angular resolution diffusion imaging (HARDI) 7‐10 dMRI data with multiple time scales of diffusion and analyze these data so as to quantify the scale of fiber grouping. While many methods have been proposed to extract information on fiber crossing 10‐26 and density morphology of white matter, 27 methods for our concern are in the early stages of development 28,29 …”
Section: Introductionmentioning
confidence: 99%